Why should I when no one else does? A review of social norm appeals to promote sustainable minority behavior - Schorn, Anna (Frontiers in Psychology, 2024)
Social norm appeals have been proven successful in promoting sustainable behavior that most people engage in. However, research on the effectiveness of social norm appeals in promoting sustainable behavior performed by a numerical minority of people is lacking. This systematic review aimed to examine empirical studies that applied social norm appeals and to elaborate on how social norm appeals could be effectively designed to foster sustainable minority behaviors. Thirty-six articles, including 54 studies, applying social norm interventions to promote sustainable minority behavior were compiled and discussed, with a particular focus on the methodology and operationalization of social norm appeals. The results showed that static descriptive minority social norm appeals might not be effective in promoting sustainable behavior. Nevertheless, there appeared to be differences depending on the strength of the norm and the environmental attitudes of the population. However, using injunctive and dynamic descriptive social norm appeals appear promising approaches because these appeals are less prone to undesirable effects. Nevertheless, it could be problematic if injunctive and descriptive social norm appeals are not aligned, but results are inconclusive. For practitioners, emphasizing social change and highlighting majority approval are simple, low-cost strategies with great potential to induce compliance and encourage sustainable minority behavior without running the risk of backfire effects.prevalent or has gained wide approval in a certain social context (Cialdini & Jacobson, 2021;Mortensen et al., 2019;Rhodes et al., 2020).According to the focus theory of normative conduct, descriptive social norm appeals (DSNAs) provide information about the proportion of people who engage in the target behavior, while injunctive social norm appeals (ISNAs) describe the proportion of people approving of the behavior within a reference group (